Evaluating knowledge of falls risk factors and falls prevention strategies among lower extremity amputees after inpatient prosthetic rehabilitation: a prospective study. Issue 16 (30th July 2020) - Hunter, Susan W.; Higa, Jordan; Frengopoulos, Courtney; Viana, Ricardo; Payne, Michael WC
Abstract: Purpose: Falls are prevalent among people with lower extremity amputations. A knowledge of risk factors is important in preventing falls, though no research has evaluated patient understanding of falls in this population. The study objective was to evaluate knowledge of falls risk factors and falls prevention strategies at discharge and 4-months after inpatient prosthetic rehabilitation. Methods: Participants completed a falls questionnaires with four sections: (1) falls during rehabilitation and after discharge, (2) falls self-efficacy using the Activities-specific Balance Confidence scale, (3) knowledge of falls risk factors, and (4) falls prevention strategies. Questionnaire responses were quantified using means and standard deviations or frequencies and percentages. Data were analyzed using paired t-tests for the Activities-specific Balance Confidence scale and the knowledge of falls risk factors, and using chi-square analyses for fall prevention strategies. Results: Twenty-seven individuals (aged 62.6 ± 8.4; 55.6% male) were included. Unsafe or risky behaviours and not paying attention to surroundings were perceived as the top two falls risk factors. Although these factors are modifiable, only 5.9% of participants listed preventative behavioural modifications. No significant differences were found in Activities-specific Balance Confidence scale scores ( p = 0.404) or knowledge of falls risk factors ( p = 0.361) between discharge and follow-up. Conclusion: This study highlights a gap between knowledge of falls risk factors and the application of knowledge to prevent falls. Follow-up data suggest that lived experience does not affect the knowledge of falls risk factors. IMPLICATIONS FOR REHABILITATION: Falls and falls prevention are an important health concern for those with lower extremityamputations and should be addressed during the rehabilitation process. Balance confidence among individuals with lower extremity amputations is low, indicating that this population is at an increased falls risk and may require intervention to prevent falls. Rehabilitation programs should encourage all forms of falls prevention modifications and strategies, such as behavioural modifications, physical activity and environmental modifications. There is a gap between knowledge of falls risk factors and how to apply this to prevent falls, which may be a target for rehabilitation.